Frontispiece: Strain Release Chemistry of Photogenerated Small‐Ring Intermediates. Issue 14 (8th March 2021) - Luque, Adriana; Paternoga, Jan; Opatz, Till
Abstract : The graphic illustrates the general principle of the reactions presented in this review. The absorption of a photon by a substrate induces the formation of a short‐lived or metastable strained intermediate (depicted in the center) which is opened under emission of a burst of strain energy to yield structurally attractive products (right‐hand side). For more details see the review by T. Opatz et al. on page 4500 .